Vedomosti a postoje rodičov v prevencii úrazov u detí predškolského veku = Parental Knowledge and Attitudes of Injury Prevention in Pre-Schoolers - Poliaková, Nikoleta; Králová, Eva; Škvareninová, Jana; Grabczak, Pavel (Vilnius: Mykolas Romeris Universitetas)
Parents are responsible for healthy development of their children. To educate children to safe childhood without injuries, it is necessary to have positive attitude and professional knowledge about the injury prevention.
Keywords: knowledge; attitude; prevention; parents; child injuries; wiedza; postawa; profilaktyka; rodzice; obrażenia dzieci